A BIMAS-Based Assessment Framework of Digital Readiness: Evidence and Institutional Patterns - Agus Pamuji; Aries Susanty; Budi Warsito (School of Computing, Telkom University, 2026)
This study examines the digital readiness of Islamic higher education institutions (IHEIs) in Indonesia in response to the intensifying demands of digital transformation, which have increasingly exposed structural constraints related to limited investment capacity, persistently low levels of digital equity, and the absence of consistent and comparable empirical evidence. Although digitalization has been widely promoted across higher education, existing assessments remain fragmented and insufficiently contextualized, thereby creating a research gap concerning how institutional readiness can be systematically evaluated within value-based educational systems. To address this gap, the study adopts the BIMAS framework as a comprehensive analytical model and applies a cross-sectional research design using a survey-based data collection approach. Methodologically, digital readiness is measured through the calculation of the Digital Readiness Index (DRI), the aggregation of the Net Promoter Score (NPS), and the qualitative evaluation of readiness levels across BIMAS dimensions. The findings, which are interpreted across seven distinct readiness levels, reveal that the Business Model, Infrastructure and Technology, and Audit and Quality Control dimensions demonstrate relatively significant developmental progress, particularly where technological adoption and procedural formalization have been prioritized.